If roots of the equation x^{2} – bx + c = 0 be two consectutive integers, then b^{2} – 4c equals

– 2

3

2

1
D.
1
Let α, α + 1 be roots
α + α + 1 = b
α(α + 1) = c
∴ b^{2} – 4c = (2α + 1)^{2}  4α(α + 1) = 1.
Sponsor Area
If roots of the equation x^{2} – bx + c = 0 be two consectutive integers, then b^{2} – 4c equals
– 2
3
2
1
D.
1
Let α, α + 1 be roots
α + α + 1 = b
α(α + 1) = c
∴ b^{2} – 4c = (2α + 1)^{2}  4α(α + 1) = 1.
Sponsor Area
The quadratic equations x^{2} – 6x + a = 0 and x^{2} – cx + 6 = 0 have one root in common. The other roots of the first and second equations are integers in the ratio 4 : 3. Then the common root is
All the values of m for which both roots of the equations x^{2} − 2mx + m^{2} − 1 = 0 are greater than −2 but less than 4, lie in the interval
If the cube roots of unity are 1, ω, ω^{2} then the roots of the equation (x – 1)^{3 }+ 8 = 0, are
The value of α for which the sum of the squares of the roots of the equation x^{2} – (a – 2)x – a – 1 = 0 assume the least value is
If roots of the equation x^{2} – bx + c = 0 be two consectutive integers, then b^{2} – 4c equals
Sponsor Area
Mock Test Series